Development of a Multiplex PCR Assay for Rapid Molecular Serotyping of Haemophilus parasuis. - Howell,KJ; Peters,SE; Wang,J; Hernandez-Garcia,J; Weinert,LA; Luan,SL; Chaudhuri,RR; Angen,Ø; Aragon,V; Williamson,SM; Parkhill,J; Langford,PR; et al. (Journal of Clinical Microbiology, 2015)
Haemophilus parasuis causes Glässer's disease and pneumonia in pigs. Indirect hemagglutination (IHA) is typically used to serotype this bacterium, distinguishing 15 serovars with some nontypeable isolates. The capsule loci of the 15 reference strains have been annotated, and significant genetic variation was identified between serovars, with the exception of serovars 5 and 12. A capsule locus and in silico serovar were identified for all but two nontypeable isolates in our collection of >200 isolates. Here, we describe the development of a multiplex PCR, based on variation within the capsule loci of the 15 serovars of H. parasuis, for rapid molecular serotyping. The multiplex PCR (mPCR) distinguished between all previously described serovars except 5 and 12, which were detected by the same pair of primers. The detection limit of the mPCR was 4.29 × 10(5) ng/μl bacterial genomic DNA, and high specificity was indicated by the absence of reactivity against closely related commensal Pasteurellaceae and other bacterial pathogens of pigs. A subset of 150 isolates from a previously sequenced H. parasuis collection was used to validate the mPCR with 100% accuracy compared to the in silico results. In addition, the two in silico-nontypeable isolates were typeable using the mPCR. A further 84 isolates were analyzed by mPCR and compared to the IHA serotyping results with 90% concordance (excluding those that were nontypeable by IHA). The mPCR was faster, more sensitive, and more specific than IHA, enabling the differentiation of 14 of the 15 serovars of H. parasuis.